A Case Series Representing Dissections in the Abdominal Aorta and Common Carotid Arteries. Issue 3 (September 2019) - Nanni, Garth S.
Dissections have the potential to occur in a variety of segments throughout the vascular tree. More than 95% of aortic dissections begin within a few centimeters of the aortic valve in the ascending aorta and beyond the branch of the subclavian artery. However, less common dissections are sometimes seen in the descending aorta. Carotid dissections are considered quite uncommon. Yet, they are estimated to be responsible for 5% to 20% of strokes in people under the age of 45. Three cases are presented, which demonstrate dissections in uncommon anatomical locations using diagnostic medical sonography and computed tomographic angiography (CTA). The first two cases demonstrate abdominal aortic dissections. The third case demonstrates a bilateral carotid dissection. One of the abdominal aortic dissections was seen clearly on corresponding CTA, while the other aortic dissection was noticed on sonography, but not on CTA. All three cases are discussed with details of patient clinical findings as well as their medical and surgical histories.